Integrated Education of Children with Intellectual Disability – Critical Review of the First Structural Changes in the Educational System - Sadowska, Sławomira (Przegląd Badań Edukacyjnych (Educational Studies Review), 2017)
The analysis refers to the idea of integrated education with its systemic solutions on the one hand, and on the other to particular actions, both open and hidden patterns of thinking and behaviours of teachers and other people connected with the introduction of these changes. Pedagogical reflection is set in certain values. On the basis of the analysis of reforms of the educational system there are mechanisms, which play a role in fulfilling the idea of justice and equality at school. As far as the students with intellectual disability are concerned, there are numerous obstructions (environmental, these concerning the strategies of learning and teaching, behavioural, organizational and administrational) presented. These obstructions make it impossible for children with intellectual disability to take full part in educational process. On this basis key issues concerning the discursive sensitivity and teaching hermeneutical reflection have been drawn.